Evaluation of the Oxidative Effect of Long-Term Repetitive Hyperbaric Oxygen Exposures on Different Brain Regions of Rats. (2nd February 2012) - Simsek, Kemal; Ozler, Mehmet; Yildirim, Ali Osman; Sadir, Serdar; Demirbas, Seref; Oztosun, Muzaffer; Korkmaz, Ahmet; Ay, Hakan; Oter, Sukru; Yildiz, Senol
Abstract : Hyperbaric oxygen (HBO2 ) exposure affects both oxidative and antioxidant systems. This effect is positively correlated with the exposure time and duration of the treatment. The present study aims enlightening the relation of HBO2 with oxidative/antioxidant systems when administered in a prolonged and repetitive manner in brain tissues of rats. Sixty rats were divided into 6 study (n = 8 for each) and 1 control (n = 12 ) group. Rats in the study groups were daily exposed 90-min HBO2 sessions at 2.8 ATA for 5, 10, 15, 20, 30 and 40 days. One day after the last session, animals were sacrificed; their whole brain tissue was harvested and dissected into three different regions as the outer grey matter (cortex), the inner white matter and cerebellum. Levels of lipid peroxidation and protein oxidation and activities of superoxide dismutase and glutathione peroxidase were measured in these tissues. Malondialdehyde, carbonylated protein and glutathione peroxidase levels were found to be insignificantly increased at different time-points in the cerebral cortex, inner white matter and cerebellum, respectively. These comparable results provide evidence for the safety of HBO treatments and/or successful adaptive mechanisms at least in the brain tissue of rats, even when administered for longer periods.